Analisis Kualitas Udara Ambien Sebelum dan Setelah Pelaksanaan Pembatasan Sosial Berskala Besar di Jagakarsa Jakarta Selatan - Andini Sri Mulyani Mulyani; Tatan Sukwika; Ninin Gusdini (Jurnal Ekologi, Masyarakat dan Sains, 2022)
The determination of Large-Scale Social Restrictions (PSBB) resulted in a decrease in community activities outside the room. On the other hand, it has an impact on reducing emission levels in the air which describes the condition of air quality in the Jagakarsa. This study was to measure ambient air quality conditions referring to the Air Pollution Standard Index (ISPU). The method of analysis is descriptive-quantitative. ISPU parameters measured were PM10, CO, SO2, NO2, and O3. All parameters were tested by paired t-test. The measurement results on the status of ambient air quality were in the "good" and "moderate" categories. The implementation of the PSBB had a significant positive impact on the PM10, NO2, and O3 parameters. About 76% of respondents gave the perception was a change in the decrease in air pollution in Jagakarsa. The conclusion of the study is that the ISPU value as long as the PSBB is in effect shows better air quality than before and or at the beginning of the PSBB implementation. Research recommendations emphasize controlling parameters that tend to fluctuate such as SO2 and CO. The policy implication is through tree planting programs or gas-absorbing gardens as a controller to maintain air quality.